Decentering Decentralization - Frug, Jerry (The University of Chicago law review, 1993)
The traditional argument holds that true decentralization of power is no longer possible. This traditional understanding of decentralized power in the US is rejected. Decentralization of power is redefined by building on the vast literature of critique of the centered subject. Two alternative visions of local government law, both organized in terms of a decentered subject, are analyzed. One way of decentering the subjectivity of localities would be to build on the literature that emphasizes that the self is formed only through a relationship with others. To build local government law on the idea of situated subjectivity, local institutions and legal doctrine must be organized in terms of inter-local relationships. One possibility would be to decentralize authority from the federal and state governments to localities under a system of rule established by a regional legislature authorized to allocate entitlements to the area's cities and suburbs.